Glasgow Sleep Effort Scale: Translation, Test, and Evaluation of Psychometric Properties of the Persian Version - Doos Ali Vand H (Dove Medical Press, 2020)
Hoda Doos Ali Vand, 1 Fahimeh Ahmadian Vargahan, 2 Morteza Charkhabi, 3, 4 Khosro Sadeghniiat Haghighi, 5 Frederic Dutheil, 6 Mojtaba Habibi 7, 8 1Department of Clinical Psychology, School of Medicine, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2School of Behavioral Sciences and Mental Health (Tehran Institute of Psychiatry), Iran University of Medical Sciences, Tehran, Iran; 3National Research University, Higher School of Economics, Moscow, Russia; 4Department of Psychology, University of Clermont Auvergne, Clermont-Ferrand, France; 5Occupational Sleep Research Center, Baharloo Hospital, Tehran University of Medical Sciences, Tehran, Iran; 6Université Clermont Auvergne, CNRS, LaPSCo, CHU Clermont-Ferrand, Clermont-Ferrand, France; 7Health Promotion Research Center, Iran University of Medical Sciences, Tehran, Iran; 8Department of Health Psychology, School of Behavioral Sciences and Mental Health (Tehran Institute of Psychiatry), Iran University of Medical Sciences, Tehran, IranCorrespondence: Mojtaba HabibiDepartment of Health Psychology, School of Behavioral Sciences and Mental Health (Tehran Institute of Psychiatry), Iran University of Medical Sciences, Mansouri St; Niayesh St; Sattarkhan Blvd, 1445613111, Tehran 14565/441, IranTel +98-21- 66551655Fax +98-21-66506853Email Habibi.m@iums.ac.irPurpose: The purpose of the current study is to translate, test and evaluate the psychometric properties of the Glasgow Sleep Effort Scale (GSES) in Persian language.Methods: Participants consisted of two samples: a clinical sample of 120 patients (58%) with insomnia disorder meeting DSM-5 criteria for insomnia and a non-clinical sample of 110 participants (42%) with normal sleep. Both samples completed the following measures: GSES, Pittsburg Sleep Quality Index, Insomnia Severity Index, Dysfunctional Beliefs and Attitudes about Sleep Scale-10, Pre Sleep Arousal Scale-cognitive subscale, Depression-Anxiety-Stress Scale-21 and sleep diary.Results: Significant correlations were found between GSES and related measures in both groups. Principal component analysis indicated a single component accounted for 64.77% of total variance in the clinical group. Results of the fit estimates for the one-factor model were consistent with the previously specified fit criteria and adequately fitted the data in the non-clinical group. Statistical analyses showed that the GSES has acceptable internal consistency in terms of Cronbach’s Alpha in the clinical (0.75) and non-clinical (0.77) samples. Test–retest reliability for a 4-week interval was significant (r = 0.70). The cut-off point, sensitivity, and specificity of the scale were 6, 85% and 94.5%, respectively.Conclusion: The Persian translated and validated version of the GSES obtained adequate values in psychometric properties in both clinical and non-clinical samples and it can be used for research and clinical purposes in Iran.Keywords: GSES, insomnia, sleep effort, psychometric properties, Persian scale